Probiotic Potential, Iron and Zinc Bioaccessibility, and Sensory Quality of Uapaca kirkiana Fruit Jam Fermented with Lactobacillus rhamnosus Yoba - Armistice Chawafambira; Moosa Mahmood Sedibe; Augustine Mpofu; Matthew Achilonu (International Journal of Food Science)
Uapaca kirkiana is an underutilised indigenous fruit tree (IFT) found in the miombo ecological zone in sub-Saharan Africa. Furthermore, sub-Saharan Africa is home to many nutritionally insecure people who suffer from micronutrient deficiency. The incorporation of probiotic strains in jams as a possible way of enhancing mineral accessibility, food quality, and health is limited in Africa. This study monitored the probiotic potential, bioaccessible iron and zinc, and organoleptic properties of U. kirkiana fruit jam fermented with L. rhamnosus yoba. U. kirkiana fruits were collected from semiarid rural areas of Zimbabwe. The L. rhamnosus yoba strain was obtained from the Yoba for Life Foundation, Netherlands. Mineral and biochemical properties of the probiotic jam were analysed using AOAC standard methods. The U. kirkiana fruit tree was ranked first as a food resource by most rural populations in Zimbabwe. The probiotic jam formulation had 55% (wt/vol) U. kirkiana fruit pulp, 43% (wt/vol) sugar, 1.25% (wt/vol) pectin, 0.5% (wt/vol) citric acid, and 0.25% (wt/vol) L. rhamnosus yoba strain. The probiotic jam had 6.2±0.2 log CFU/mL viable L. rhamnosus yoba cells. Iron and zinc content (mg/100 g w.b.) was 4.13±0.22 and 0.68±0.02 with pH 3.45±0.11, respectively. Nutrient content was g/100 g w.b., carbohydrate 66±4.1, fat 0.1±0.01, crude protein 0.2±0.01, ash 0.7±0.02, and crude fiber 0.3±0.01. Bioaccessible iron and zinc were 6.55±0.36% and 16.1±0.50% and increased by 4% and 2% in the probiotic jam, respectively. Mineral bioaccessibility and nutrient content were significantly different (p<0.05) in jam with 0.25% L. rhamnosus yoba. Jam acceptance rating was 83%. The probiotic jam can be used as a sustainable food containing probiotic with potential nutritional and health benefits.